P690 Comparative efficacy of vedolizumab and adalimumab as second-line therapy in ulcerative colitis patients previously treated with infliximab. (25th January 2019) - Favale, A; Onali, S; Caprioli, F; Pugliese, D; Armuzzi, A; Macaluso, F S; Orlando, A; Viola, A; Fries, W; Mocci, G; Chicco, F; Usai, P; et al.
Abstract: Background: Adalimumab (ADA) and Vedolizumab (VDZ) have shown efficacy in moderate to severe ulcerative colitis (UC) patients who failed Infliximab (IFX). Though, a comparative efficacy evaluation of ADA and VDZ in this clinical setting is currently missing. Aim: to compare the efficacy of ADA and VDZ in patients affected by UC who failed the first-line therapy with IFX. Methods: Clinical records of UC patients from 8 Italian IBD referral centres, who failed IFX given for active luminal disease and candidate to receive a second-line biologic with either ADA or VDZ were retrospectively reviewed. Clinical variables, including reason for IFX discontinuation, clinical activity and therapy duration were recorded. The proportion of patients still on therapy at Week 52 was evaluated as primary endpoint. The failure-free survival was analysed by univariate and multi-variate analysis. Secondary endpoints included therapy discontinuation at Week 8, 24 and 52, discontinuation-free survival and safety. Results: Of 161 UC patients (15 [9%] primary, 87 [52%] secondary failures to IFX and 63 [39%] IFX intolerants), 64 (40%) received ADA and 97 (60%) VDZ as second-line therapy. At Week 52, 37.5% and 28.9% of patients on ADA and VDZ, respectively, showed therapeutic failure ( p = 0.302). However, the failure rate was significantly higher in the ADA- when compared with VDZ group among IFX secondary failures (48.0% ADA vs. 22.4% VDZ, p = 0.035). The therapy discontinuation-free survival was significantly higher in the group of IFX secondary failures who received VDZ when compared with ADA at both the univariate ( p = 0.007) and multi-variate survival analysis (OR 2.6; 95% CI 1.11–5.98; p = 0.028). No differences in the failure and biologic discontinuation-free survival was observed in the IFX primary failure and intolerant subgroups. Conclusions: VDZ might be the therapy of choice in those UC patients who showed secondary failure to IFX.